2014
DOI: 10.1007/s00345-014-1374-6
|View full text |Cite
|
Sign up to set email alerts
|

Nocturia and its impact on health-related quality of life and health care seeking behaviour in German community-dwelling men aged 50 years or older

Abstract: Our study confirmed that nocturnal voiding is highly prevalent in community-dwelling men and reduce both physical and mental health status. Bother from nocturnal voiding is the most relevant component of LUTS responsible for medical consultations in German men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 23 publications
4
34
0
2
Order By: Relevance
“…In men >70 years of age, the prevalence rates of nocturia ≥1 times per night rose to 68.9-93.0 % and ≥2 times per night to 29.0-59.3 %. This topic issue of the World Journal of Urology on nocturia also contains the first report on nocturia in German community-dwelling men in which 87 % of men aged 50-80 years reported about nocturia ≥1 times per night and 43 % of men ≥2 times per night [5]. This study confirmed the high prevalence rates in Germany and is in line with the results of other epidemiological studies.…”
Section: Epidemiologysupporting
confidence: 80%
See 3 more Smart Citations
“…In men >70 years of age, the prevalence rates of nocturia ≥1 times per night rose to 68.9-93.0 % and ≥2 times per night to 29.0-59.3 %. This topic issue of the World Journal of Urology on nocturia also contains the first report on nocturia in German community-dwelling men in which 87 % of men aged 50-80 years reported about nocturia ≥1 times per night and 43 % of men ≥2 times per night [5]. This study confirmed the high prevalence rates in Germany and is in line with the results of other epidemiological studies.…”
Section: Epidemiologysupporting
confidence: 80%
“…Although the perception of bother associated with nocturia largely depends on the individual, the FINNO study reported bother from nocturia when the individual has to void at least 2 times per night (i.e., clinically relevant nocturia) [3]. The German epidemiological study on nocturia, first presented in this topic issue, confirmed this threshold value in adult men and showed that ≥2 voids per night significantly reduces HRQoL (as measured by the SF-12 questionnaire and the IPSS-QoL index) and is the only symptom of all LUTS captured on the IPSS questionnaire that triggers medical consultations in the 2-year follow-up period [5]. The higher the nocturnal voiding frequency was, the more deteriorated the HRQoL became.…”
Section: Health-related Quality Of Lifementioning
confidence: 63%
See 2 more Smart Citations
“…Healthcare-seeking behavior is triggered by LUTS severity and LUTS phenotypes. Men often consult their doctors when they have severe LUTS or experience urinary urgency or nocturia [1,3]. LUTS/BPH have a multifactorial etiology and can be caused by the prostate, bladder, urethra, pelvic floor, central or peripheral nervous system, ureters, or even by the kidneys in case of nocturnal polyuria [4].…”
mentioning
confidence: 99%